Murder on the orient express eaudiobook - Christie, Agatha (Hercule Poirot, 2013)
THE MOST WIDELY READ MYSTERY OF ALL TIME — NOW A MAJOR MOTION PICTURE DIRECTED BY KENNETH BRANAGH AND PRODUCED BY RIDLEY SCOTT! "The murderer is with us—on the train now . . ." Just after midnight, the famous Orient Express is stopped in its tracks by a snowdrift. By morning, the millionaire Samuel Edward Ratchett lies dead in his compartment, stabbed a dozen times, his door locked from the inside. Without a shred of doubt, one of his fellow passengers is the murderer. Isolated by the storm, detective Hercule Poirot must find the killer among a dozen of the dead man's enemies, before the murderer decides to strike again. "What more . . . can a mystery addict desire?"— New York Times